Strategi Competitive Advantage Media Online: Studi Terhadap Lkbn Antara Biro Jambi - Putri, Salwa; Aziz, Arfan (UIN Sulthan Thaha Saifuddin Jambi, 2024)
News is an essential need for an information-hungry society. With the rapid development of technology, online media competition is getting tougher. To survive, LKBN Antara Jambi Bureau needs a strategy to gain a competitive advantage. This research uses descriptive qualitative methods with observation, interview, and documentation techniques. Three informants were selected through purposive sampling. Data were analyzed using the Miles and Huberman method, including data presentation, data reduction, and verification. The results showed that LKBN Antara Jambi Bureau has the main strategies: first, managing human resources (HR) through training and welfare guarantees; second, developing innovations to increase funding and strengthen positions in the media industry; third, providing complete facilities in each office to support journalists' activities, such as laptops and vehicles. This strategy supports LKBN Antara to remain competitive in the media industry.